Seasonal freeze-thaw characteristics of soil carbon pools under different vegetation restoration types on the Longzhong Loess Plateau - Liu, Shuainan; Wu, Jiangqi; Li, Guang; Yang, Chuanjie; Yuan, Jianyu; Xie, Mingjun (Frontiers in Ecology and Evolution, 2022)
Soil carbon pools are important for maintaining the stability of the carbon cycle in terrestrial ecosystems and regulating climate change. However, it is not clear how soil carbon pools change under different vegetation restoration types at high altitudes during frequent seasonal freeze-thaws (FTs). Therefore, we studied the seasonal FT variability (before freezing, early stages of freezing, stable freeze stage, thawing stage) of soil organic carbon (SOC), microbial biomass carbon (MBC), dissolved organic carbon (DOC), and easily oxidized organic carbon (EOC) under three vegetation restoration types (Grassland, GL; Caragana korshinskii, CK; Xanthoceras sorbifolia, XS) on the Longzhong Loess Plateau region. We found that during the seasonal FT, the 0-40 cm SOC, MBC, DOC, and EOC contents were higher in XS vegetation than in GL and CK vegetation, but the sensitivity index of SOC was lower in XS vegetation (sensitivity index = 2.79 to 9.91). In the 0-40 cm soil layer, the seasonal FT process reduced the MBC content and increased the DOC content in the three vegetation soils. Meanwhile, DOC and EOC contents accumulated obviously in the stable freezing period and decreased significantly in the thawing period. We also found that the SOC, MBC, DOC, and EOC contents were higher in the surface soils (0-10 cm) than in the underlying soils (10-20, 20-40 cm), while the sensitivity of the soil carbon pool fractions to seasonal FT processes differed considerably between soil depths. Redundancy analysis (RDA) showed that soil total nitrogen, temperature, total phosphorus, and soil water content were important environmental factors influencing soil carbon pool fractions during seasonal FT. This study suggested that in the Longzhong Loess Plateau region, soil MBC and DOC were more susceptible to seasonal FT phenomena and that the soil system of the Xanthoceras sorbifolia vegetation had a stronger soil C sequestration function during the seasonal FT process.